Study of Optimum Cutting While Lathing Carbonate Steel VCN-150 Uses a Layered Carbide Chisel PVD on Dry and Wet Condition - R. Harahap, Muksin; Bakhori, Ahmad; Napid, Suhardi; Rafiq Yanhar, Muhammad; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
To improve the productivity of this machining perhaps it may be recommended in a dry cutting but a dry cutting is recognized very sensitive to a high temperature. In this case, in order to overcome is perhaps required by using a tool carbide either in layers or without any layers whereby each layer has certain superior. There was conducted an experiment to have an optimum cutting on a carbon steel VCN-150 using a layers tool carbideÂ  and Respond Surface Method (RSM) with a CCD operation. The result of study recommended that condition optimum cutting shall be achieved (When cutting tc ) on a medium machining refers to ISO 3685 and medium surface roughness (Ra ) ISO 1320. Statistically, there is no found significant difference between a dry and wet cutting on optimum dry condition.Â Â